PEMILU BERSIH: ANTARA HARAPAN DAN KENYATAAN - Gunawan, Deni (Jurnal Keadilan Pemilu, 2023)
Elections are a celebration of the people's democracy and should be conducted honestly and openly. The primary objective of elections is to identify leaders who are able to improve the condition of society, particularly for those who have difficulties fulfilling their own and their families’ basic needs. Indonesians expect elections to be a path to prosperity, as mandated by the 1945 Constitution. However, elections in Indonesia still face various difficult challenges that must be faced by all Indonesians. One of them is the existence of fraudulent practices that are difficult to fully control by the state, in this case, the election organizers. These fraudulent practices occur on all sides: organizers, voters, and election participants. They are intertwined with each other. The apathy of the public towards the organization of elections is one of the reasons. Another reason is the massive practice of money politics. The high demand for money in society increases the risk of manipulation by those with financial power during elections. This is a serious threat to the future of Indonesian democracy. A successful election is crucial for the advancement of Indonesian democracy. As a sovereign country, elections are a way for Indonesia to achieve the ideals of prosperity for all its citizens.